2005
DOI: 10.1007/bf03178708
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of an II based and a flat panel based cardiovascular fluoroscopy system within a clinical environment

Abstract: The image quality and dose parameters from a 2004 Siemens Axiom Artis dBC cardiac biplane with flat panel detector were evaluated and compared to similar parameters evaluated for a 1977 Toshiba DPF 2000A biplane cardiac unit with a conventional image intensifier. Image quality assessment was performed with the Westmead test object; using solid water as a patient equivalent absorber. The patient dose comparison of the two systems is based on dose area product meter readings for 1512 patient cases recorded over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Frequently, DAP meters were not found to account for table attenuation [48,54], consequently the correct DAP and skin dose to the patient may be lower than the values reported in this study. A solid-state detector was used to determine the table-top attenuation at various tube angulations.…”
Section: Appendixmentioning
confidence: 56%
See 1 more Smart Citation
“…Frequently, DAP meters were not found to account for table attenuation [48,54], consequently the correct DAP and skin dose to the patient may be lower than the values reported in this study. A solid-state detector was used to determine the table-top attenuation at various tube angulations.…”
Section: Appendixmentioning
confidence: 56%
“…Flat-panel detectors are purported to have better detector quantum efficiency (DQE), and are therefore able to reduce radiation dose to the patient [46,47]. Clinical studies have shown that digital flat-panel systems produce images at similar or higher quality than conventional imaging intensifiers, although some studies reported no significant difference in the radiation exposure delivered between flat-panel detectors and conventional image intensifiers [47,48]. However, Prasan et al [49] and Tsapaki et al [50] found a greater radiation exposure with flat-panel detectors: Prasan and colleagues [49] reported a 35% difference when compared with image intensifiers.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Some studies have proposed an increase in radiation whilst others have failed to document a difference. It is unclear if any difference in radiation exposure for the two systems can be wholly explained by differences in pulse rate and field size or whether it is attributable to an intrinsic property of the flat-panel imaging system.…”
Section: Introductionmentioning
confidence: 97%
“…Some papers have reported values on pediatric patient doses for cardiac procedures (Boothroyd et al 1997, Campbell et al 2005, Rassow et al 2000, Schultz et al 2003, Bacher et al 2005 but data are still scarce to determine reference levels like those available for adults in diagnostic and therapeutic procedures (Neofotistou et al 2003). In addition, the recent introduction of dynamic flat panel detectors (FD) for x-ray systems used in cardiology could allow a reduction of patient doses whilst maintaining or improving the image quality (ICRP 2004, Vano et al 2005, Balter 2004, Spahn 2005, Holmes et al 2004, Grewal and McLean 2005, Tsapaki et al 2005, 2004. This paper presents a set of patient dose values in four age bands, measured in a pediatric catheterization laboratory equipped with a biplane x-ray system with dynamic FDs and cardiologists properly trained in radiation protection.…”
Section: Introductionmentioning
confidence: 99%